EMPLOYEE WORK DICIPLINE AT PT. BRUNSIA SAMUDRA TULUNGAGUNG - Binti Luklukah; Arisyahidin Arisyahidin; Eka Askafi; Ratna Dewi Mulyaningtiyas (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Work discipline is the willingness and awareness of employees to obey and comply with the regulations and norms that apply within the company. The aim of this research is to analyze employee work discipline at PT. Brunsia Samudra Tuluanggung. The research method is qualitative. The location of the research was at PT. Brunsia Samudra is domiciled in Kalipakis Hamlet, RT. 001 RW. 002 Pucung Lor Village, Ngantru District, Tulungagung Regency, research time was January - February 2025, data collection in this study used primary data, namely interviews, documentation, observation and secondary data, namely data taken from PT. Brunsia Samudra. There were 7 informants in this study, namely commissioners, operators, administration and verifiers, administration, operator assistants, data analysis using qualitative analysis. The results of this research are the discipline aspect. This research states that the level of employee discipline in the attendance aspect is quite good, although there are obstacles because some employees are still in college, this can be overcome by arranging work schedules so that employee tasks can be completed efficiently. OK, then the employee's punctuality is quite good, although the problem is that some employees are quite far between where they live and the office. This can be overcome by coaching and giving rewards to disciplined employees.